Size and Ambundance of glass eel Anguilla spp in mouth of Poigar River - Kristanto R. Lumi; Victor N. R. Watung; Nego E. Bataragoa (Jurnal Ilmiah PLATAX, 2019)
The  aims of this study are determine the composition of the length and abundance of glass eel Anguilla spp that migrates at the mouth of the Poigar River. Sampling is done every month for four months in the new moon phase. Sampling site on one side of the Poigar River estuary, by making a 10 meter track in the direction of the river flow. The fishing gear used is a triangle-shaped handy scoop net with a length of 100 cm and a width of 75 cm. The catch of Glass eel eel for four months (from April to July 2018) as many as 3,551 individuals. Average length (± SD) in April was 44.4 ± 1.4 cm, May 48.7 ± 1.6 cm, June 51.1 ± 2.0 cm and July 51.1 ± 2.4 cm. The highest number of catches in May was 1,841 individuals, followed by June 785, July 860 individuals and April as many as 55 individuals. The average density of eels in April, Mai, June and July 2018 migrating in the sampling area of 10 x 0.7 meters is 1,160 individuals.Keywords: glass eel, size, abundance, Poigar River.ABSTRAKPenelitian ini bertujuan untuk mengetahui komposisi ukuran panjang dan kelimpahan  ‘‘glass eel’’ sidat Anguilla spp yang bermigrasi di muara Sungai Poigar.  Pengambilan sampel dilakukan setiap bulan selama empat bulan pada  fase  bulan baru. Tempat sampling  pada  satu sisi muara Sungai Poigar, dengan membuat lintasan sepanjang 10 meter searah aliran sungai. Alat tangkap yang digunakan adalah seser (handy scoop net) berbentuk segitiga dengan panjang 100 cm dan lebar 75 cm. Hasil tangkapan Glass eel sidat selama empat bulan (dari bulan April sampai Juli 2018) sebanyak 3.551 individu.  Rata-rata  panjang (± SD) pada bulan April 44,4±1,4 cm, Mei 48,7±1,6 cm, Juni 51,1±2,0 cm dan Juli 51,1±2,4 cm.  Jumlah tangkapan terbanyak pada bulan Mei 1.841 individu, diikuti bulan Juni 785, bulan Juli 860 individu dan bulan April sebanyak 55 individu.  Rata-rata kepadatan sidat pada bulan April, Mai, Juni dan Juli 2018 yang bermigrasi dalam wilayah sampling 10 x 0,7 meter adalah 1.160 individu.Kata kunci: glass eel, ukuran, kelimpahan, Sungai Poigar.